Aplicabilidade da termografia infravermelha para quantificar a temperatura facial durante a mastigação - MELO, ANA TATIANA GONZALEZ DE (2024)
Infrared Thermography is a useful, painless, noninvasive and non-ionizing imaging technique that detects the distribution of heat on the body surface, recording and transforming into images the infrared radiation emitted by the skin, which can contribute significantly to aid in the diagnosis and planning of numerous orofacial alterations. The objective of this research was to evaluate the applicability of Infrared Thermography to quantify facial temperature before and after chewing, measuring the temperature of the masseter and anterior temporal muscles. This research was approved by the Research Ethics Committee of UEPB under CAAE 80009824.4.0000.5187. This was a cross-sectional, analytical and quantitative study, carried out at the Infrared Thermography Laboratory (LTI) of the Department of Dentistry of the State University of Paraíba - UEPB - Campus I. The sample consisted of 47 volunteers from spontaneous demand, recruited from the Department of Dentistry. The research was conducted in three stages: 1st stage - Recruitment/screening/guidance, 2nd stage - interview and data collection and the 3rd stage - the thermographic examination itself, before and after chewing Trident® gum for 2 minutes. After the application of the Fonseca Anamnesis Questionnaire and data collection, the volunteers received recommendations for preparation for the acquisition of thermographic images and were scheduled for a subsequent thermographic examination at the LTI of UEPB. The images were acquired using a portable thermal camera with an infrared sensor FLIR T650sc Infrared, at a distance of 80 cm from the volunteer, in three moments. First, when the volunteer arrived at the laboratory, in a second moment, after chewing the gum for 2 minutes, and in the third moment, 20 minutes after the second intervention, during the muscle rest period. Nine thermographic acquisitions were performed for each volunteer, divided as follows: frontal, right lateral and left lateral norms at each moment mentioned above. The thermographic images were analyzed using the FLIR Thermal Studio software to thermographically evaluate the influence of chewing on the masseter and anterior temporal muscles. Forty-seven female volunteers with a mean age of 27 years and 51.1% of whom were white were evaluated. Descriptive statistical analysis characterized the sample. Repeated Measures Analysis of Variance (ANOVA-MR) was selected to evaluate muscle temperature scores before the intervention (pre-test), 2 minutes after the intervention (post-test) and 20 minutes after the intervention (follow-up). Then, Bonferroni's post-hoc test was used to identify the difference between groups. The assumption of sphericity was assessed using the Mauchly test. When violated, the Greenhouse-Geisser or Huynh-Feldt corrections were applied. For the temporal muscle, since the normal distribution of residues was not observed, the Fridman test was used and, subsequently, the Wilcoxon Signed Rank test to assess the difference between groups. Most participants did not present temporomandibular dysfunction (40.4%), and among those with dysfunction, the mild degree was the most frequent (34%). Regarding the Body Mass Index (BMI), 27% were within the normal weight. Chewing caused an increase in facial temperature in the regions analyzed, which showed a reduction in temperature shortly after follow-up. The chewing test increases the diagnostic efficiency of the thermographic examination to aid in the diagnosis of TMDs.